Optimizing Pharmacological Management of Lower Urinary Tract Symptoms in Frail Elderly Patients within a Home-Based Primary Care Program - Murtaza Maqbool Khanbhati, Anum Ashraf, Ayesha Tahir, Nadeem Akhtar Korai, Syed Raza Abbas, Asma Ali (Pakistan Journal of Medical & Health Sciences, 2023)
Aim of Study: To evaluate the efficacy of a structured pharmacological protocol for managing lower urinary tract symptoms (LUTS) in frail elderly patients within a home-based primary care program, focusing on symptom reduction, medication safety, and quality-of-life improvement. Study Duration: January 2022 to March 2023. Study Place: Rai Foundation Medical College, Sargodha & Niazi Medical & Dental College, Sargodha. Study Type: Prospective quasi-experimental study (pre-post intervention). Methodology: 150 frail patients (aged ≥65, Clinical Frailty Scale ≥5) with moderate-to-severe LUTS received a 12-week tailored pharmacological intervention. The protocol included deprescribing high-risk medications (e.g., anticholinergics), initiating guideline-based therapy (e.g., α-blockers, mirabegron), and biweekly telehealth monitoring. Outcomes were assessed using the International Prostate Symptom Score (IPSS), Anticholinergic Cognitive Burden (ACB) scale, and EuroQol-5D (EQ-5D) at baseline, 6 weeks, and 12 weeks. Results: IPSS scores decreased from 20.4 ± 3.1 (baseline) to 11.2 ± 2.8 (12 weeks; *p* < 0.001). ACB scores reduced from 3.8 ± 1.2 to 1.5 ± 0.9 (*p* < 0.001). EQ-5D improved from 0.52 ± 0.12 to 0.78 ± 0.10 (*p* < 0.001). 32% reduction in LUTS-related hospitalizations compared to pre-intervention. Discussion: Protocol-driven management significantly improved LUTS control while reducing polypharmacy risks. Home-based telehealth enabled real-time dose adjustments, enhancing adherence and safety. Conclusion: Integrating deprescribing, targeted pharmacotherapy, and telehealth monitoring optimizes LUTS management in frail elderly patients, reducing symptoms and healthcare utilization. Keywords: Lower urinary tract symptoms, frail elderly, home-based primary care, deprescribing, anticholinergic burden, telehealth, pharmacological management.